Novos juízos sobre a política: desvelando preconceitos a partir do pensamento de Hannah Arendt: - Cabral, Rafael Leite Ferreira (2019)
The theme of this research is the making of new judgments about politics, which is based on the thought of Hannah Arendt, who, in view of the rupture of the tradition of political philosophy, sought the original political experiences from which political thought developed since Plato unlinked. The problem to be faced is the meaning of politics and what is the significance of politics today. The approach of the Author's work has the general objective of clarifying the preconceptions towards politics that permeate the tradition, demonstrating how Arendt faced them and presenting their original political conceptions. This path, despite the fragmentary and problematic character of his work, is traced from the decantation of his lines of thought and exposed in a structured way through the distinction between the philosopher's contemplative vita and the citizen's active vita and the development of activities, inherent in the human condition, of labor, work and action. Having exposed these fundamental questions of the author's thought, it is possible to achieve the specific objectives of the work that consist in the development of political conceptions originating from plurality, freedom, and public space that, linked to action and discourse, allow the formation of new judgments about politics. Based on this theoretical tool, we confront the preconceptions and crises that underlie pessimism against politics and the difficulties of its exercise in contemporary societies, by defending the following hypotheses: a) preconceptions against politicians and their replacement by managers who can to impress capitalist efficiency in the state bureaucracy (no one's government) is based both on the instrumental perspective of politics, as a means to an end, and on the platonic distinction between rulers and ruled, characteristic of the human activity of the work; b) the narrowing of political spaces in which human plurality can show itself, in which man can act and speak among equals in order to constitute the world through the diversity of perspectives; c) co-optation of the political system by external factors (economy and justice) that prevent men from expressing themselves politically; d) alienation and standardization of human behavior in work and consumption, which stifles the spontaneity of men, restricts plurality and therefore drastically affects politics in mass societies; e) the identification of election and representation with politics, which results in the removal of the people from politics and, therefore, in the privatization of public spaces and public affairs. The result is the conclusion that politics embodies the condition of reality and legitimacy of man, the world, thought and collective decisions, so that, although it is problematic in view of the period we live in explicit preconceptions and even repulsion against politics, politics remains indispensable if it is still intended to give a reliable meaning to the world and political affairs.